Perfection of State Control and Supervising Activity in the Russian Federation - Aleksandrovna Zavalko, Natalia; Vladimirovna Panina, Olga; Lvovna Krasyukova, Natalia; Vitalievna Bratarchuk, Tatyana; Alekseevich Fedulin, Aleksandr (International Journal of Engineering and Technology, 2018)
The article is devoted to the development of approaches to perfection of state control and su-pervising activity in the Russian Federation. It has been established that state control and supervising activity of public authorities is administrative activity that is expressed in a complex of actions aimed at supervision, compliance of accomplishment and adherence to legal orders by entities under control. It has been proved that new economic relationship that is being formed in the state requires new approach to implementation of control and supervising functions. It has been defined that significant overregulation of entities under control, first of all economic entities, insufficient certainty of supervisory powers of supervising entities lead to creation of illegal framework resulting in mistakes and abuse of control and supervising authorities. It has been established that reformation of control and supervising activity should be by way of legislative delineation of control from other kinds of activities similar in forms and purpose.Â